Microplastics Occurrence in Surface Waters and Sediments in Five River Mouths of Manila Bay - Osorio, Ezra D.; Tanchuling, Maria Antonia N.; Diola, Ma. Brida Lea D. (Frontiers in Environmental Science, 2021)
Microplastics have been increasingly documented globally in numerous environmental compartments. However, little information exists in the Philippines despite the fact that the country is considered to be one of the largest contributors of plastics in oceans. This study, considered as one of the pioneering microplastic research, evaluated the abundance, distribution, and composition of microplastic pollution in the mouths of five rivers, namely Cañas, Meycauayan, Parañaque, Pasig and Tullahan, draining to Manila Bay. Surface water and sediments samples were collected, then passed through a stack of sieves with sizes from 2.36 mm at the top to 0.075 mm at the bottom. These samples were digested to remove organic matter, and salt solutions were added to allow the microplastics to float. Extracted particles were examined under a stereo microscope, and quantified and categorized into shape, size, color, and type. Results show that microplastics were present ubiquitously at all river mouths but with concentrations varying from 1,580 to 57,665 particles/m3 (surface water) and 386 to 1,357 particles/kg (dry sediment). Fragment was the most abundant shape, while white, blue, and transparent were the most prevalent colors. Fourier Transform Infrared Spectroscopy (FTIR) analysis revealed that polypropylene (PP), high and low-density polyethylene (high-density polyethylene and low-density polyethylene) and polystyrene were the main types of microplastics present in the river mouths.